EVALUATION OF THE FATTY ACIDS AND AMINO ACIDS PROFILES IN SPENT GRAIN FROM BREWING AND MALT WHISKY - ANCUȚA CHETRARIU; VASILE FLORIN URSACHI; ADRIANA DABIJA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The food industry generates huge amounts of food by-products annually, most of which are considered waste. But these by-products may contain nutrients of interest and have a low-cost price. Capitalizing on these by-products is of interest to both producers and consumers, thus supporting the circular economy. In this context, the current paper aimed to evaluate the fatty acid profile and the amino acid profile of spent grain from distilleries compared to spent grain coming from the beer industry. The main fatty acids were identified linoleic, palmitic, and oleic acids. Amino acids are necessary for the production of enzymes, hormones, and even some neurotransmitters, being considered the most important nutrients of the human body. The most abundant essential amino acid is valine in both samples analyzed and the lowest level of essential amino acid is tryptophan for distilleries spent grain (DSG) and leucine for brewery spent grain (BSG).